2019
DOI: 10.1371/journal.pone.0211818
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endurance training and testosterone supplementation on the expression of blood spinal cord barrier proteins in rats

Abstract: The present study aimed to estimate the effect of endurance training, two doses of testosterone, and the combination of these stimuli on the level of the endothelial proteins claudin, occludin, JAM-1, VE-cadherin, ZO-1, ZO-2, and P-glycoprotein in rat spinal cords. Adult male Wistar rats were trained using a motor-driven treadmill for 6 weeks (40–60 min, 5 times per week) and/or were treated for 6 weeks with two doses of testosterone (i.m.; 8 mg/kg or 80 mg/kg body weight). Spinal cords were collected 48 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The increase in BBB permeability after depletion of T is due to loss of expression of tight junction proteins such as claudin-5 and ZO-1 [37]. Conversely, a recent study shows that T supplementation for 6 weeks to young adult male Wistar rats compromises the blood spinal cord barrier as shown by a reduced expression of tight junction proteins, such as occludin, Jam 1, and VEcadherin in the spinal cord [38]. This indicates that androgens' effects on the blood barrier could be regionspecific.…”
Section: Blood-brain Barriermentioning
confidence: 98%
“…The increase in BBB permeability after depletion of T is due to loss of expression of tight junction proteins such as claudin-5 and ZO-1 [37]. Conversely, a recent study shows that T supplementation for 6 weeks to young adult male Wistar rats compromises the blood spinal cord barrier as shown by a reduced expression of tight junction proteins, such as occludin, Jam 1, and VEcadherin in the spinal cord [38]. This indicates that androgens' effects on the blood barrier could be regionspecific.…”
Section: Blood-brain Barriermentioning
confidence: 98%
“…In human and mouse renal cell culture, estradiol increased digoxin clearance, and P‐gp/ Abcb1 expression, while testosterone had no effect 57 . However, at the blood‐spinal cord barrier of rats, testosterone supplementation in vivo led to increased P‐gp protein expression 58 . In male guinea pigs, testosterone levels during the post‐natal androgen surge peak at around PND3 59 ; it is possible that high levels of testosterone have a positive regulatory effect on P‐gp, leading to sexual dimorphism in transporter expression and function.…”
Section: Discussionmentioning
confidence: 95%
“…57 However, at the blood-spinal cord barrier of rats, testosterone supplementation in vivo led to increased P-gp protein expression. 58 In male guinea pigs, testosterone levels during the post-natal androgen surge peak at around PND3 59 ; it is possible that high levels of testosterone have a positive regulatory effect on P-gp, leading to sexual dimorphism in transporter expression and function. There is a wide range of evidence supporting sex differences in drug metabolism in adults, 60 however, literature in the neonate is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chen et al (2011) suggested that T had a detrimental effect following intracerebral hemorrhage‐induced brain injury in rats. Nierwińska et al (2019) have found that the excessive supply of T may have an adverse effect on the expression of endothelial proteins in the nervous system, which in turn may affect the functioning of the blood–brain barrier. As in the case of T, too low or too high a concentration of E 2 induces the process of apoptosis in cells (Harms et al, 2001).…”
Section: Discussionmentioning
confidence: 99%